The Effect of Murottal and Lavender Aromatherapy on Post-Circumition Pain in Pediatric Patients at Oerip Putra Brebes Clinic - Anditya Daffa; Susana Widyaningsih (UM Purwokerto Press, 2024)
Background: Circumcision is a medical procedure involving the removal of the prepuce, resulting in wound and significant postoperative pain that disrupts daily activities. The use of nonsteroidal anti-inflammatory drugs (NSAIDs) to manage pain has associated side effects, prompting the exploration of non-pharmacological therapies such as murottal and aromatherapy as alternatives for pain management in post-circumcision pediatric patients. Method: This quantitative study utilized a pre-experimental design with a one-group pre-and-post-test approach. A sample of 20 respondents was selected using non-probability purposive sampling at Oerip Putra Brebes Clinic. Pain level was measured using the Wong-Baker Faces Pain Rating Scale. The respondents were being asked three times for the pain scale before the intervention, to make sure the pain scale is not temporarily but it’s their final answer. Data analysis employed the Wilcoxon Signed Rank Test. Data collection was condcuted between December 2022 and February 2023. Results: The average pain scale value before intervention was 4,20, and after intervention, it was 4,70. The Wilcoxon test yielded a p-value of 0,197, indicating no significant impact from murottal and lavender aromatherapy on post-circumcision pediatric patients. Conclusion: The administration of murottal and lavender aromatherapy did not yield a significant impact on post-circumcision pain in pediatric patients.